Roles of Strong Scalar Couplings in Maximizing Glutamate, Glutamine and Glutathione Pseudo Singlets at 7 Tesla - An, Li; Evans, Jennifer W.; Burton, Courtney; Tomar, Jyoti S.; Ferraris Araneta, Maria; Zarate, Carlos A.; Shen, Jun (Frontiers in Physics, 2022)
For the H4 protons of glutamate (Glu), glutamine (Gln), and the glutamyl moiety of glutathione (GSH), the effect of the internal strong scalar coupling between the two nonequivalent H4 protons is far greater than that of the external couplings between the H3 and H4 protons. In this work, the roles of the internal and external scalar coupling terms in the dependence of Glu, Gln, and glutamyl GSH H4 peak amplitudes on the placement of the refocusing pulses of the point resolved spectroscopy sequence were investigated by full density matrix simulations. These strong coupling effects allowed practical and approximately simultaneous maximization of the sensitivity of the spectrally resolved Glu, Gln, and glutamyl GSH H4 pseudo singlets for spatially localized in vivo detection of Glu, Gln, and GSH in the human brain using magnetic resonance spectroscopy at the magnetic field strength of 7 Tesla.